Identity and Immigrant Stereotypes: A Study Based on the Ego-Ecological Approach. Issue 2 (3rd April 2018) - Mannarini, Terri; Procentese, Fortuna
ABSTRACT: Based on the ego-ecological approach, which views identity as deeply interconnected with the social environment via group memberships, this study reconstructed the psychosocial identity of a group of Sri Lankan immigrants who settled in Naples, Italy, with the aim of detecting resonances between their self-representations and the stereotypes circulating in the receiving society. Fifty-one Sri Lankan immigrants completed a shortened version of the Multistage Investigator of Social Identity (MISI) with the following two stimulus groups: "Sri Lankans" (i.e., ethnocultural identity) and "immigrants." Analyses revealed an implication of the self in both groups (i.e., Sri Lankans and immigrants), with the represented immigrant self more negatively connoted than the ethnocultural self. The contents of the self-representations showed resonances with both the stereotypes associated with immigrants in Italian society and the specific stereotype associated with the Sri Lankan community, thereby empirically confirming that in the immigrant experience identity feels the effect of the attitudes of the receiving context.